Skenario Pembelajaran dengan Ular Tangga untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa di Kelas VII MTsN 2 Aceh Timur - Zaratuzar (Jurnal Aktual Pendidikan Indonesia, 2023)
This study aims to enhance the engagement and learning outcomes of 7th-grade students at MTsN 2 Aceh Timur through the implementation of a learning scenario based on the "Snakes and Ladders" game. The research method employed is Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. Data were collected using observation sheets to measure student engagement and learning tests to assess the improvement in understanding the material. Data analysis was carried out descriptively and quantitatively to determine the development of student engagement and learning outcomes from one cycle to the next. The results showed a significant increase in student engagement during the learning process. Additionally, there was an improvement in student learning outcomes, as indicated by the increase in the average student scores in each cycle. The application of the learning scenario based on the "Snakes and Ladders" game proved effective in creating a more interactive and enjoyable learning environment, which ultimately had a positive impact on students' learning outcomes.